Dublin Jewish demography a century ago - O Grada, Cormac (Economic & Social Studies, 2006)
This paper examines the demography of Ireland?s Jewish community a century ago. Its focus is on Dublin Jewry, then mainly a community of immigrants from the Tsarist Empire and their children. It compares the marital fertility and infant and child mortality of immigrant couples with those of native couples living in the same neighbourhood. While `economic? variables are shown to have mattered, there remains a large `cultural? component to the distinctive demography of Jewish households.
Presented at the Conference on Macroeconomic Perspectives in Honour of Brendan M. Walsh, held at University College Dublin on 7 October, 2005
Keywords: Dublin; Jewry; Demography; Jewish community